Maintenance Electroconvulsive Therapy in a Patient with Treatment-Resistant Paranoid Schizophrenia and Comorbid Epilepsy - Beppe Micallef-Trigona; Joseph Spiteri (Case Reports in Psychiatry)
The treatment of choice for acute schizophrenia is antipsychotic drug treatment and electroconvulsive therapy (ECT) and should only be considered as an option for treatment-resistant schizophrenia, where treatment with clozapine has already proven ineffective or intolerable. The use of ECT as a maintenance treatment for patients with schizophrenia and comorbid epilepsy is uncommon as scant evidence exists to support this. We describe a patient with a serious case of paranoid schizophrenia and comorbid epilepsy who had not responded to typical and atypical antipsychotic medication, but responded remarkably to acute ECT and required maintenance ECT to sustain a positive therapeutic response.